Wideband Balun-LNAs using asymmetric CCC technique for WLAN and mobile WiMAX applications. (August 2019) - Kishore, K. Hari; Venkataramani, B.; Raju, B. Kasi
Abstract: Capacitive Cross-Coupling (CCC) buffers require the output impedances of their drivers to be equal. For drivers with unequal output impedances such as the CG-CS balun-LNA, an asymmetric CCC technique denoted as A-CCC is proposed in this paper. Two Wideband Balun LNAs– LNA1 which uses A-CCC and an auxiliary current reuse amplifier (ACRA), and LNA2 which uses A-CCC, ACRA and shunt peaking are proposed to achieve noise figure (NF) less than 2 ​dB. The proposed LNAs are implemented in 0.18 ​μm CMOS technology and are evaluated through post-layout simulations. It is found that NF, Gain, 3dB band of (1.81–2.5 ​dB, 23.7–26.7 ​dB, 1 – 4 ​GHz) and (1.97–4.14 ​dB, 25–28 ​dB, 1 – 6 ​GHz) are obtained for LNA1 and LNA2 respectively. The average IIP3, IIP2 of LNA1 and LNA2 are found to be (−8.45 dBm, +11.73 dBm) and (−2.59 dBm, +17.42 dBm). The LNA1 and LNA2 consume 6.7 ​mW and 6.53 ​mW power from a 1.2 ​V supply for core areas of 0.25 ​mm 2, 0.85 mm 2 .